MAP Kinase Pathways in Brain Endothelial Cells and Crosstalk with Pericytes and Astrocytes Mediate Contrast-Induced Blood-Brain Barrier Disruption - Yuki Matsunaga; Shinsuke Nakagawa; Yoichi Morofuji; Shinya Dohgu; Daisuke Watanabe; Nobutaka Horie; Tsuyoshi Izumo; Masami Niwa; Fruzsina R. Walter; Ana Raquel Santa-Maria; Maria A. Deli; Takayuki Matsuo (MDPI AG, 2021)
Neurointervention with contrast media (CM) has rapidly increased, but the impact of CM extravasation and the related side effects remain controversial. This study investigated the effect of CM on blood-brain barrier (BBB) integrity. We established in vitro BBB models using primary cultures of rat BBB-related cells. To assess the effects of CM on BBB functions, we evaluated transendothelial electrical resistance, permeability, and tight junction (TJ) protein expression using immunohistochemistry (IHC) and Western blotting. To investigate the mechanism of iopamidol-induced barrier dysfunction, the role of mitogen-activated protein (MAP) kinases in brain endothelial cells was examined. We assessed the effect of conditioned medium derived from astrocytes and pericytes under iopamidol treatment. Short-term iopamidol exposure on the luminal side induced transient, while on the abluminal side caused persistent BBB dysfunction. IHC and immunoblotting revealed CM decreased the expression of TJ proteins. Iopamidol-induced barrier dysfunction was improved via the regulation of MAP kinase pathways. Conditioned medium from CM-exposed pericytes or astrocytes lacks the ability to enhance barrier function. CM may cause BBB dysfunction. MAP kinase pathways in brain endothelial cells and the interactions of astrocytes and pericytes mediate iopamidol-induced barrier dysfunction. CM extravasation may have negative effects on clinical outcomes in patients.